Storm time response of the midlatitude thermosphere: Observations from a network of Fabry‐Perot interferometers. Issue 8 (12th August 2014) - Makela, Jonathan J.; Harding, Brian J.; Meriwether, John W.; Mesquita, Rafael; Sanders, Samuel; Ridley, Aaron J.; Castellez, Michael W.; Ciocca, Marco; Earle, Gregory D.; Frissell, Nathaniel A.; Hampton, Donald L.; Gerrard, Andrew J.; et al.
Abstract Observations of thermospheric neutral winds and temperatures obtained during a geomagnetic storm on 2 October 2013 from a network of six Fabry‐Perot interferometers (FPIs) deployed in the Midwest United States are presented. Coincident with the commencement of the storm, the apparent horizontal wind is observed to surge westward and southward (toward the equator). Simultaneous to this surge in the apparent horizontal winds, an apparent downward wind of approximately 100 m/s lasting for 6 h is observed. The apparent neutral temperature is observed to increase by approximately 400 K over all of the sites. Observations from an all‐sky imaging system operated at the Millstone Hill observatory indicate the presence of a stable auroral red (SAR) arc and diffuse red aurora during this time. We suggest that the large sustained apparent downward winds arise from contamination of the spectral profile of the nominal thermospheric 630.0 nm emission by 630.0 nm emission from a different (nonthermospheric) source. Modeling demonstrates that the effect of an additional population of 630.0 nm photons, with a distinct velocity and temperature distribution, introduces an apparent Doppler shift when the combined emissions from the two sources are analyzed as a single population. Thus, the apparent Doppler shifts should not be interpreted as the bulk motion of the thermosphere, calling into question results from previous FPI studies of midlatitude storm time thermospheric winds. One possible source of contamination could be fast O related to the infusion of low‐energy O+ ions from the magnetosphere. The presence of low‐energy O+ is supported by observations made by the Helium, Oxygen, Proton, and Electron spectrometer instruments on the twin Van Allen Probes spacecraft, which show an influx of low‐energy ions during this period. These results emphasize the importance of distributed networks of instruments in understanding the complex dynamics that occur in the upper atmosphere during disturbed conditions.